Pharmacokinetics in Morbid Obesity: Influence of Two Bariatric Surgery Techniques on Paracetamol and Caffeine Metabolism - Goday Arno, Albert; Farré, Magí; Rodríguez-Morató, Jose; Ramon, Jose M.; Pérez-Mañá, Clara; Papaseit, Esther; Civit, Ester; Langohr, Klaus; lí Carbó, Marcel; Boix, David Benaiges; Nino, Olga Castañer; Le Roux, Juana Antonia Flores; et al. (Obesity surgery, 2017)
Purpose The purpose of the study was to study the impact of the two most common bariatric surgery techniques on paracetamol pharmacokinetics (a marker of gastric emptying) and caffeine metabolism (a marker of liver function). Materials and Methods In the present prospective study, we studied 24 morbid obese patients before, at 4 weeks, and 6 months after having undergone sleeve gastrectomy ( n = 10) or Roux-en-Y gastric bypass ( n = 14). For comparative purposes, 28 healthy controls (14 normal weights and 14 overweights) were also included in the study. Results Paracetamol pharmacokinetics was altered in the obese participants leading to lower bioavailability. Bariatric surgery resulted in faster absorption and normalized pharmacokinetic parameters, prompting an increase in paracetamol bioavailability. No differences were found between surgical procedures. In the case of caffeine, the ratio paraxanthine/caffeine did not differ between morbid obese and healthy individuals. This ratio remained unmodified after surgery, indicating that the liver function (assessed by cytochrome P450 1A2 activity) was unaffected by obesity or bariatric surgery. Conclusions Paracetamol pharmacokinetics and caffeine plasma levels are altered in severely obese patients. The two studied bariatric surgical techniques normalize paracetamol oral bioavailability without impairing the liver function (measured by cytochrome P450 1A2 activity).